2020
DOI: 10.4187/respcare.07076
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Ventilation Measured by Electrical Impedance Tomography in Critically Ill Children

Abstract: BACKGROUND: Electrical impedance tomography (EIT) is a noninvasive, portable lung imaging technique that provides functional distribution of ventilation. We aimed to describe the relationship between the distribution of ventilation by mode of ventilation and level of oxygenation impairment in children who are critically ill. We also aimed to describe the safety of EIT application. METHODS: A prospective observational study of EIT images obtained from subjects in the pediatric ICU. Images were categorized by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…In summary, these results, measured by a case-control trial with a crossover of two ventilation modes, revealed that EIS did not appear to reliably measure changes of impedance between NAVA and SIMV (PC) PS, when both, single and butterfly electrodes, are used in one study group. In addition, various studies have also shown a lack of comparison of ventilation modes by different methods [20,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these results, measured by a case-control trial with a crossover of two ventilation modes, revealed that EIS did not appear to reliably measure changes of impedance between NAVA and SIMV (PC) PS, when both, single and butterfly electrodes, are used in one study group. In addition, various studies have also shown a lack of comparison of ventilation modes by different methods [20,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…e children's nutritional risks have not been screened in time. us, the malnutrition of critically ill children is neglected [10][11][12][13] X ± s). e horizontal axis from left to right represents before intervention and after intervention, and the vertical axis represents the IgG level (μmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…12 The lower elastic recoil in children may further cause a shift to the more anterior parts of the lung. 29 Recently, Inay and colleagues reported 30 similar findings on the coefficient of variation in 25 children who had either CSV or no positive-pressure support. However, they also reported that under controlled ventilation the coefficient of variation was more directed toward the nondependent zones.…”
Section: Discussionmentioning
confidence: 78%